Perancangan Interior Pusat Fitness dan Kalistenik di Surabaya - Salim, Christianto (Intra, 2015)
Interior design of Fitness Center and Calisthenics in Surabaya is a project designed upon the background to provide a facility that is capable of meeting the exercise needs of the people in Surabaya. Society is not just exercising with the facilities but also feel comfortable. In addition, people are also introduced to the calisthenics sport which is becoming a trend. The planned facilities include a fitness room, lounge, calisthenics room, aerobics room, steam room, whirlpool, locker room, cafÃ© and lobby, This design leads to the circulation and distribution of a well designed room with a semi-outdoor atmosphere.